HUKUM ISTRI MENCARI NAFKAH DALAM TINJAUAN MAQASHID SYARIAH - Elimartati Elimartati (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
In common tradition, making a living is a husband's obligation, but now many wives play a role in earning a living. The aim of the study was to find out the law of the wife looking for a nafka, viewed the condition and ability of the husband to provide a living, in the review of Maqashid Shari'a proposed by Syatibi. The influence of science and technology and the increase in household needs triggers many wives to take part in making a living, and become the main breadwinner. This certainly raises the question, how does the view of Islamic law on wives earn a living in library research, using the normative qualitative method of gender analysis approach is content analysis. Islamic law explains that a wife cannot leave her house without her husband's permission and her main task is at home. This certainly raises the question, how does the view of Islamic law on wives earn a living. The results of the study explain that wife's law makes a varied living circumcision, makhruh and haram based on the ability of the husband to provide his wife with the benefit and the level of family needs (maqashid).